Concepção dos professores sobre o uso de jogos virtuais em tempos de pandemia - Frois, Rodrigo Valbueno (Universidade Federal de São Carlos, 2021)
Didactic games stimulate several areas of the brain circuits, from the interpretation of images such as the storage and improvement of vocabulary to strategies in relation to the specific theme addressed by the game. It is worth mentioning the importance of the social interaction that the games bring among its participants and once they are chosen and applied as a pedagogical resource, they often end up being satisfactory for learning a certain content outside or inside the classroom. However, in pandemic times, WHO recommends social distance and remote classes to meet the needs of students during the 2020 school year. Thus, we tried to transform the physical game into digital format and faced some difficulties due to lack of resources and understanding of computer graphics. In this way, the present work aims to verify how basic education teachers are dealing with these situations at this moment, and what are their understandings regarding virtual didactic games. And we conclude that although teachers use and think they are a good helper in teaching and learning students, there is still a need for projects involving both technology professionals and specific teachers in the field in order to develop better games that include fun and motivating specific content.
Teachers' conception of the use of virtual games in times of pandemic
Keywords: Ensino de ciências; Ensino remoto; Jogos didáticos e virtuais; Pandemia; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM